The relationship between the forward and realised spot exchange rate in South Africa - Chris van Heerden; André Heymans (Journal of Economic and Financial Sciences, 2012)
It is well known that the forward exchange rate and the realised future spot exchange rate differ. This phenomenon is better known as the exchange rate puzzle. Two approaches were followed to ascertain whether this difference is due to the weak explanatory ability of current economic fundamentals or whether the use of an ineffective econometric approach to model exchange rate theories is to blame. The first approach makes use of stationary economic time series data to model the ZAR/USD realised future spot exchange rate, while the second uses non-stationary level economic data to model the ZAR/USD realised future spot exchange rate. While the first approach reported weak results, the second approach illustrated that economic fundamentals are able to explain the ZAR/USD realised future spot exchange rate. These results also confirm that the exchange rate puzzle is a pseudoproblem.